(untitled) (International Journal of Food and Nutritional Sciences, 2022)
HRM performs all the activities of an organization with the hope to attain the individual and organizational goals, the employees’ employment life cycles stages are handled effectively with the help of human resource practices, which have direct impact on the employees’ satisfaction on their work. Though private hospitals are filled with the big pool of human capital, still it lacks to tap the full potential of their employees. Therefore an attempt has been made to understand whether the existing human resource practices are much enough to enhance the potentiality of the employees and increase the performance. The aim of the present study was to investigate impact of Human Resource Management on the performance of employees of private hospitals in Kanyakumari district. The study aims to know the level of satisfaction of employees towards Human Resource Management of private hospitals. The present study is based on both primary data and secondary data. The primary data were collected through the questionnaire from the employees working in private hospitals in Kanyakumari district. 75 samples of employees were taken from private hospitals in Kanyakumari District. Well designed questionnaire was used for getting the responses of employees working in private hospitals in Kanyakumari district. It is found that experience wise there is a significant difference in satisfaction towards human resource management of private hospitals namely recognition and job security factor, grievance redressal and motivation factor and suggestion and control system factor.